DIVERSITY OF BENTHIC MACROINVERTEBRATES AND STREAMS QUALITY IN THE NATIONAL PARK OF BELEZMA (NORTHERN-EAST, ALGERIA) - Benzina, Imène; Bachir, Abdelkrim (LIFE: International Journal of Health and Life-Sciences, 2018)
In North Africa, the studies of streams quality are incomplete, especially in arid environments which are very fragile. This work is intended to highlight the knowledge of the health status of the streams in the Belezma National Park (Biosphere Reserve) through a multi-parametric approach based on benthic macroinvertebrates ecology. We have prospected in April 2015 four temporary rivers (Wadis: W. Hamla, W. Chaaba, W. Bouilef and W. El Ma) and evaluated the biodiversity of benthic macroinvertebrates in relation to a set of environmental factors: 12 physicochemical water parameters, global habitat characteristics and degree of human pressure. The water flow velocity is generally very low to medium. The habitats are dominated by coarse substratum and rocks (5-90%), sand and gravel are poorly represented while plants habitats are completely absent. The water pH was between 7.29 and 8.50, nitrates (0 - 0.76) and nitrites (0.1 - 0.4). The water was slightly salted (0.20% and 0.30%) and generally clear (turbidity: 2.8 to 22 NTU). We identified a total of 28 taxa of benthic macroinvertebrates divided into 3 phylums, 4 classes, 11 orders and 22 families. Among the insect class, which was the most dominant taxa, the most abundant groups are Diptera (36.85%), Trichoptera (20.92%) and Ephemeroptera (16.73%). The highest biodiversity (total richness: 22 taxa; Shannon index: 2.84) was noted in W. Chaaba, which is located in the integral zone of the protected area. The evaluated biotic index of water quality ‘’IBGN’’ shows that hydro-biological quality of the water in the 4 studied streams was generally as ‘’average’’ (IBGN score between 9 and 10). It would be urgent to set up a biomonitoring program in order to control the disturbances issue to high pollution in this protected area.